Indonesian journal of learning and instruction - Universitas Kuningan. Fakultas Keguruan dan Ilmu Pendidikan; Universitas Kuningan. Sekolah Pascasarjana (Faculty of Teacher Training and Education in collaboration with School of Postgraduate Studies, Universitas Kuningan, 2018)
Critical issues of educational practices in primary, secondary and tertiary education as well as in university level.
Keywords: Education : Indonesia : Periodicals; Education : Periodicals; Education; Indonesia